Respiratory properties of whole blood and hemoglobin from the burrowing reptile, Amphisbaena alba - Johansen, K.; Abe, A. S.; Weber, R. E. (Wiley, 1980)
Respiratory properties of whole blood and hemoglobin solutions have been studied in the burrowing reptile, Amphisbaena alba. Whole blood is distinguished from that of other squamate reptiles by an extraordinary high O2 affinity (P50 = 12 mmHg at pH 7.60 and 25°C). The Bohr factor,ϕ, was large at −0.85 and the n‐value was 1.80. O2 capacity averaged 12.0 vol%. The molar concentration of erythrocyte ATP was high and twice that of hemoglobin. Stripped Amphisbaena hemoglobin shows an extremely high O2 affinity and reduced pH sensitivity compared to whole blood (P50 = 1 mmHg at pH 7.60 and 25°C, ϕ = −0.35, n‐value = 2.0). The hemoglobin O2 affinity was much more sensitive to ATP than for other poikilotherm vertebrates. Isoelectric focusing revealed a multicomponent hemoglobin with the major components showing similar O2 affinities and Bohr shifts. The data obtained are discussed in relation to the burrowing habits of Amphisbaena and found to be adaptive to a fossorial mode of life. Copyright © 1980 Wiley‐Liss, Inc., A Wiley Company